A one-dimensional coordination polymer based on Cu3-oximato metallacrowns bridged by benzene-1, 4-dicarboxylato ligands: structure and magnetic properties1. Issue 17 (7th May 2015) - Croitor, Lilia; Coropceanu, Eduard B.; Petuhov, Oleg; Krämer, Karl W.; Baca, Svetlana G.; Liu, Shi-Xia; Decurtins, Silvio; Fonari, Marina S.
<x xml:space="preserve">Abstract</x> A one-dimensional linear coordination polymer {[Cu3(μ3-OH)(2-pyao)3(bdc)]·6(H2O)}n (1) composed of trinuclear metallacrown cores has been obtained.